Strategi Transformasi Digital dalam Meningkatkan Keunggulan Kompetitif UMKM di Era Ekonomi Digital - Muhammad Yusuf, Fadhil (Jurnal Manajemen dan Bisnis Kreatif, 2026)
The digitization shift has developed into a strategic foundation for Micro, Small, and Medium Enterprises (MSMEs) to sustain competitiveness within the electronic commerce landscape. However, many business entities continue to encounter obstacles in adopting digital tools, including limited technological competencies, financial constraints, and the absence of well-structured policy frameworks. This study focuses on examining the contribution of digitization shift policies to enhancing the competitive advantage of business entities. The study employs a qualitative approach through a literature review, drawing on scientific articles, research reports, and academic publications published between 2021 and 2025. The findings indicate that the digitization shift increases operational productivity, fosters business model innovation, and expands market networks through digital platforms, including online commerce and digital promotion. The digitization shift also strengthens customer interaction through data-driven policies and the integration of technological tools. The results further reveal that the success of the digitization shift requires the implementation of sound policy governance, institutional readiness, and continuous adaptation of technological systems. The implications of this study suggest that business entities need to design integrated digital policies and enhance technological capabilities in order to maintain business performance and competitive advantage within the electronic commerce landscape.